Challenges Facing Teaching Arabic Language in Elementary Schools in the Central West Bank, Palestine as Seen by Principals, Supervisors and Teachers - Smoom, Linda Walid; Fteiha, Ahmad (Dirasat: Educational Sciences, 2021)
The current study aims to identify the challenges of teaching and learning Arabic for students at public elementary schools in the central West Bank as seen by the principals, supervisors and teachers, and to identify the suggestions of these groups to develop the process of teaching and learning Arabic. The researcchers used a quantitative approach with a descriptive survey design, and a qualitative approach with an analytical descriptive design. A questionnaire and semi-structured interviews were adopted as tools for the study. The questionnaire was distributed to a simple random sample of public schools in the central West Bank, in the academic year (2017/2018), whose size was 129 schools out of (193). Three models of semi-structured interviews were also adopted, and they were directed to an accessible sample of principals, supervisors and teachers of Arabic for the elementary stage, which included seven principals, four supervisors, and ten teachers. The results showed that the most prominent challenges of teaching and learning Arabic are the overlap between colloquial and standard Arabic, and the decline in the status of Arabic in scientific fields, As for the most prominent proposals, it was necessary to strengthen the role of parents and increase communication between them and the school, and to employ the Internet in the process of teaching and learning Arabic language, by designing websites and applications for Arabic language curricula.